ASYNCHRONOUS DEVELOPMENT OF REEFS AND REEF-BUILDING BIOTA. PALEOZOIC - V. G. Kuznetsov (Известия высших учебных заведений: Геология и разведка)
This work analyses the development of reefs, which represent thick morphologically expressed carbonate massifs created by the activity of frame-forming organisms. Major stages in the development of reefs include the periods of Early Cambrian, Ordovician, Silurian-Devonian, Late Viséan-Serpukhovian and Permian, the upper boundaries of which are generally determined by mass extinction events.The main reef builders during the Early Cambrian were archaeocyatha and epiphytaceans, while Ordovician reefs were created by sponges, stromatoporoids, tabulata and bryozoans. Stromatoporoid, tabulata, rugose and, to a lesser extent, bryozoans were the reef builders during the longest Silurian-Devonian period. Bryozoans and corals served as the frame-forming organisms for Upper Viséan-Serpukhovian reefs. However, during the Permian, reefs were built primarily by sponges and, to a lesser extent, by bryozoans and corals.It is shown that there is no strict correspondence between the termination of reef formation and the beginning of extinction events. During extinction periods, potential reef builders did exist, although beyond the reef biocoenosis structure. Similarly, the beginning of reef formation occurs somewhat later than the appearance of the corresponding frame-forming organisms. Apparently, it takes time for organisms to develop such a biocoenosis that could trigger the formation of reef ecosystems. Reef ecosystems are stable under relatively constant external conditions, changes in which cause first the degradation of the biocoenosis and then the extinction of its constituent organisms. Therefore, the process of reef formation is terminated before the actual extinction of organisms.